The Effect of Black Tax on Employee Engagement: The Mediating Role of Idiocentrism-Allocentrism-A Case of Pharmaceutical Industry in Zimbabwe - E., Vakira; D., Nikisi; N., Ndlovu; V., Shumba; M., Ncube, C.; D., Mpofu, B. (Journal of Economics and Behavioral Studies, 2021)
Employees in the Pharmaceutical industry are coming late to work and knocking off early. These actions unveiled by the employees are likely to incur economic costs on the employer, occasioned by low employee productivity. Owners of production have expressed concern over the general low staff morale in the pharmaceutical sector. While most studies have concentrated on internal job-related factors as drivers of employee engagement, this study seeks to assess employee engagement as being influenced by black tax, an external factor. The main aim of the research was to establish the influence of black tax on employee engagement, being mediated by idiocentrism-allocentrism, particularly focussing on the pharmaceutical manufacturing and retailing industry in Bulawayo, Zimbabwe. The study employed the philosophical approach of pragmatism to guide the whole research. The researcher adopted a multi-stage sampling technique supported by the census technique to pick participants from the population. Closed and open-ended questionnaires were used to collect data from qualified pharmacists who are working in both the manufacturing and retailing industry in Bulawayo. Statistical Package for Social Sciences v23 (Process v3.5 by Andrew F. Hayes) was used to test the hypothesized relationship among variables. Qualitative data were analyzed using thematic analysis. The results suggest that black tax directly influence employee engagement in the presence of a mediator (idiocentrism-allocentrism). Furthermore, the results indicate that the indirect coefficient was partially significant, which means that idiocentrism-allocentrism has a partial influence on employee engagement. The researchers recommend that management should ensure that employees are motivated all the time. They should implement an open-door policy so that employees can share their issues that affect their engagement level at work.